Comparison of findings on thoracic computed tomography with the severity and duration of bronchial asthma in patients with eosinophilic granulomatosis with polyangiitis. (June 2018) - Nakamoto, Keitaro; Saraya, Takeshi; Ogawa, Yukari; Ishii, Haruyuki; Takizawa, Hajime
Abstract: Background: Eosinophilic granulomatosis with polyangiitis (EGPA) is a systemic necrotizing vasculitis with eosinophilia. EGPA can occur in patients with comorbid bronchial asthma (BA) and other pulmonary diseases. However, because of its rarity, there are few reports on thoracic computed tomography (CT) findings in patients with EGPA, especially in relation to comorbid BA. The aim of this study was to compare between the clinical characteristics of EGPA, the severity and duration of BA, and the findings on thoracic CT. Methods: We retrospectively reviewed the records of patients with EGPA who were admitted to our hospital from 2001 to 2015. All patients satisfied the criteria for EGPA according to American College of Rheumatology or Lanham's criteria. Patients without asthma (n = 2) and those in whom CT was not performed (n = 3) were excluded. Results: We identified 31 patients who had EGPA comorbid with BA. The median duration of BA was 6 years. CT revealed parenchymal opacification (ground-glass opacity and/or consolidation; n = 17), airway abnormalities (bronchial wall thickening and/or bronchiectasis; n = 15), pleural effusion (n = 4), interlobular septal thickening (n = 5), and mediastinal lymphadenopathy (n = 4). Importantly, the group with severe BA had a significantly higher incidence of airway abnormalities than the group with mild to moderate BA (81.8% vs 30.0%, P  = 0.009). The frequency of airway abnormalities was significantly higher in patients with EGPA who had a history of asthma of 5 years or more than in their counterparts with a shorter asthma history (66.7% vs 10.0%, P  = 0.006), particularly bronchial wall thickening (52.4% vs 10.0%, P  = 0.046). Conclusions: The most common finding on thoracic CT in patients who had EGPA comorbid with BA was parenchymal opacification followed by airway abnormalities. The severity and duration of BA in these patients may affect the findings on thoracic CT.